Compliance with children's television food advertising regulations in Australia - Roberts Michele; Pettigrew Simone; Chapman Kathy; Miller Caroline; Quester Pascale (BMC, 2012)
Abstract Background The objective of this study was to assess the effectiveness of the Australian co-regulatory system in limiting children's exposure to unhealthy television food advertising by measuring compliance with mandatory and voluntary regulations. An audit was conducted on food and beverage television advertisements broadcast in five major Australian cities during children's programming time from 1st September 2010 to 31st October 2010. The data were assessed against mandatory and voluntary advertising regulations, the information contained in an industry report of breaches, and the Australian Guide to Healthy Eating. Results During the two months of data collection there were a total of 951 breaches of the combined regulations. This included 619 breaches of the mandatory regulations (CTS) and 332 breaches of the voluntary regulations (RCMI and QSRI). Almost 83% of all food and beverages advertised during children's programming times were for foods classified as 'Extras' in the Australian Guide to Healthy Eating. There were also breaches in relation to the amount of advertising repetition and the use of promotional appeals such as premium offers, competitions, and endorsements by popular children's characters. The self-regulatory systems were found to have flaws in their reporting and there were errors in the Australian Food and Grocery Council's compliance report. Conclusions This audit suggests that current advertising regulations are inadequate. Regulations need to be closely monitored and more tightly enforced to protect children from advertisements for unhealthy foods.